Cancer Targeted Therapy Strategy: The Pathologist's Perspectives - Alessandrini, Lara; Perin, Tiziana; Kadare, Shahin; del Pup, Lino; Memeo, Lorenzo; Steffan, Agostino; Colarossi, Lorenzo; Berretta, Massimiliano; De Paoli, Paolo; Canzonieri, Vincenzo (Current Cancer Drug Targets, 2018)
The effectiveness of new personalized treatment procedures in oncology is based on the fact that certain tumors exhibit specific molecular features. More in detail, neoplastic tissues of patients should display a specific biomarker, most often a specific genetic alteration and/or under/overexpression of a definite protein, that could be the target of its respective drug. Immunohistochemical and molecular analyses, which usually include examination of nucleic acids from either tissues or fluids, are common tests to define the status of a tumor. This review focuses on the pathologist's role in carefully controlling pre- analytic procedures and standard operating procedures that are a crucial prerequisite to reach reliable and reproducible results. Six paradigmatic applications of targeted therapy, for which pathological diagnosis plays a fundamental role, are summarized. Traditional and next-generation sequencing are also addressed from the pathologist's perspective as well as the importance pathologists have in this shift to more accurate definition of disease risk and prognostication of therapy response in the personalized medicine era.
Keywords: molecular analyses